ANALISIS PENGARUH SENTIMEN INVESTOR, TINGKAT SUKU BUNGA, NILAI TUKAR DAN CONTAGION EFFECT TERHADAP IHSG - Vietha Devia SS; Salsabila Nasyiha Al Sakinah (Contemporary Studies in Economic, Finance and Banking, 2022)
Investment is an activity to delay consumption, with the aim of getting added value in the future. Currently, the development of investment in Indonesia has increased greatly, as seen from the movement of the Jakarta Stock Exchange Composite Index (JKSE) which has occurred during the last 5 years has experienced a significant increase. The movement of the Jakarta Stock Exchange Composite Index (JKSE) is influenced by several factors. This study aims to determine how the influence of investor sentiment, exchange rate, BI Rate and Contagion Effect on the Jakarta Stock Exchange Composite Index (JKSE). The research method used in this research is Multiple Regression Analysis and Vector Error Correction Model. The results of this study indicate that there is a positive influence between Investor Sentiment and Jakarta Stock Exchange Composite Index (JKSE), Exchange Rates have a negative effect on Jakarta Stock Exchange Composite Index (JKSE), while the BI Rate has no effect on the Jakarta Stock Exchange Composite Index (JKSE). The ASEAN Stock Exchange Index has a long-term relationship with the Jakarta Stock Exchange Composite Index (JKSE) and is integrated with each other.